O Paraguai na agenda externa brasileira e a temática de Itaipu: 2003-2010 - Paula, Orlando Fernandes de [UNESP] (2014)
During the 1960s and 1970s Brazil and Paraguay undertook the construction of Itaipu, generating consequences in relations with Argentina. The power struggles in the platinum region would only be resolved in the late 1970s. In the 1980s and 1990s Brazil and Paraguay have joined mechanisms for regional integration that approached the two countries. In this period Itaipu has always remained as a topic on the bilateral agenda. In the first decade of this century the change of government in Brazil since 2003 declared the priority to South America and represented a new phase in the bilateral relationship with new agreements and new tensions between the two countries. In Paraguay the end of Colorado Party in the Executive in 2008 catalyzed forces that have always been in opposition to claim firmly the revision of the Treaty of Itaipu, resulting in hard negotiations over nearly a year. Thus this paper seeks to analyze the Brazilian foreign policy during the Lula government when the political changes in both countries were processed. The Itaipu topic pervades Brazilian foreign agenda. The hypothesis is that Brazil ceded in the Paraguayan pressures since the first studies on Seven Falls to the 2009 agreement, for a strategy to attract and keep the Guarani country under its influence. Under Lula Brazil had already approached the government of Nicanor Duarte Frutos and after the rise of Fernando Lugo, Brazil was very comprehensive with the aim of preserving the regional integration project and maintain Paraguay near. However this did not mean that the Paraguayan demands were completely satisfied.